Analisis Desain Modular Mata Bajak Singkal untuk Meningkatkan Kemudahan Perawatan dan Perbaikan - Gafar, Arvan; Waskito Waskito (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
The use of moldboard plows in agricultural land preparation often faces wear problems on the share component, leading to increased maintenance time and reduced operational efficiency. This study aims to design and analyze a modular concept for the plow share to improve maintenance and repair efficiency without compromising structural performance. The research methods include field observation, component dimension measurement, design modeling using CAD software, and structural analysis using the Finite Element Analysis (FEA) method. In addition, maintenance ease was evaluated through a questionnaire based on a rating scale. The results show that the modular design significantly improves maintenance and repair efficiency, with an average score of 4.59 categorized as very good. Structural analysis indicates that the modular design reduces maximum stress on the moldboard and slightly decreases deformation, reflecting improved structural stiffness compared to the conventional design. However, the Safety Factor on the share component remains below the acceptable limit, indicating the need for further development. Overall, the modular design provides an effective solution to enhance maintenance efficiency while maintaining the structural performance of the moldboard plow.